Strategies for Preserving Rujak Soto Banyuwangi as a Culinary Cultural Heritage and Local Tourist Attraction - Achmad Taufiq; Bawa Mulyono Hadi (Transpublika Publisher, 2025)
This research aims to formulate preservation strategies for Rujak Soto Banyuwangi as a culinary cultural heritage capable of supporting local tourism attraction development. The methodology employed is a descriptive qualitative approach through interview techniques, observation, literature studies, as well as SWOT analysis and Business Model Canvas (BMC). The research findings indicate that Rujak Soto has great potential as a local culinary icon with unique flavors and strong cultural values, but faces challenges including minimal national recognition, lack of documentation, and changing consumer preferences. The proposed preservation strategies include strengthening culinary identity through digital promotion, developing culinary-based tourism villages, business operator training, and integration into tourism packages. The implications of this research emphasize the importance of collaboration between government, business operators, and the younger generation in preserving traditional cuisine as part of strengthening the local economy and cultural diplomacy. The originality of this study lies in integrating financial management dimensions, MSME financing strategies, and sustainable business model innovations in culinary preservation efforts, which have not been extensively explored in previous studies in the context of local Indonesian tourism.